2022
DOI: 10.2147/jir.s326896
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Non-Surgical Periodontitis Therapy on the Clinical Features and Serological Parameters of Patients Suffering from Rheumatoid Arthritis as Well as Chronic Periodontitis

Abstract: Objective: The present study aims to evaluate the effects of basic periodontal disease therapy on the general condition and serum inflammatory indicators of patients with rheumatoid arthritis (RA) combined with chronic periodontitis (CP). Methods: Forty patients with RA were enrolled in the study and, based on the results of an oral examination and in line with the 2018 periodontitis diagnostic criteria, they were divided into a group with CP (the RA + CP group) and a group without CP (the RA group). Twentynin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(41 reference statements)
2
13
0
Order By: Relevance
“…The mean value of all the periodontal parameters such as plaque index, modified gingival index, probing pocket depth, and clinical attachment levels was found higher in group RA + P when compared to other groups (Table 1). This was in accordance with the studies done by Gamel et al (2017) and Ding et al (2022). In the study done by Ding et al (2022), significant difference was found in all the periodontal parameters and the serological indicators in the RA + CP group compared with those in the CP, RA, and controls.…”
Section: Discussionsupporting
confidence: 94%
“…The mean value of all the periodontal parameters such as plaque index, modified gingival index, probing pocket depth, and clinical attachment levels was found higher in group RA + P when compared to other groups (Table 1). This was in accordance with the studies done by Gamel et al (2017) and Ding et al (2022). In the study done by Ding et al (2022), significant difference was found in all the periodontal parameters and the serological indicators in the RA + CP group compared with those in the CP, RA, and controls.…”
Section: Discussionsupporting
confidence: 94%
“…NSPT can effectively decrease bacteria, bacterial antigens, and pro-in ammatory mediators that invade the circulatory system 15 . The reduction of systemic in ammation observed after NSPT seems to contribute to a better clinical outcome of RA 43 . Herein, we observed that previous studies showed a signi cant decrease in the DAS28 after NSPT 19,20,21,22 which was con rmed by our meta-analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Four articles on RA were excluded because they lacked data on control patients, while one SLE study by Marques et al. was excluded as it enrolled patients with dental diseases as controls ( 33 , 52 , 53 , 71 , 75 ). Figure 4A depicts the network diagram.…”
Section: Resultsmentioning
confidence: 99%